ENERGY EFFICIENCY OF CULTIVATION OF CUCUMBER ON THE SEED GOALS IN EASTERN FOREST-STEPPE OF UKRAINE - Вітанов, О. Д.; Солдатенко, О. В.; Урюпіна, Л. М. (Scientific Progress & Innovations, 2014)
It is established that when the cultivation of cucumber seed goals in Eastern forest-Steppe of Ukraine the best way to drip irrigation is. For this method of irrigation fertilizers must be applied locally in soil based N30P60K45 and conduct fertigation twice during the vegetation period on the N15. The obtained yield of conditioned seeds (188 kg/ha) at the lower energy costs (352,7 MJ) on the formation of 1 kg of seeds, and the largest energy efficiency ratio (0,053) by saving water (46 %) and mineral fertilizers (50 %).